2022
DOI: 10.1186/s12904-022-01099-9
|View full text |Cite
|
Sign up to set email alerts
|

Low rates of structured advance care planning documentation in electronic health records: results of a single-center observational study

Abstract: Background Proper advance care planning (ACP) documentation both improves patient care and is increasingly seen as a marker of high quality by governmental payers. The transition of most medical documentation to electronic health records (EHR) allows for ACP documents to be rapidly disseminated across diverse ambulatory practice settings. At the same time, the complexity and heterogeneity of the EHR, as well as the multiple potential storage locations for documentation, may lead to confusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…This study supports use of multilevel interventions in tertiary, academic settings, where clinician-level interventions alone may be less effective for ACP . Unlike prior work in community clinics, in which LHW approaches alone were tested, in this study, we found no effect on frequency of ED use or the proportion of participants with ED use.…”
Section: Discussionsupporting
confidence: 69%
“…This study supports use of multilevel interventions in tertiary, academic settings, where clinician-level interventions alone may be less effective for ACP . Unlike prior work in community clinics, in which LHW approaches alone were tested, in this study, we found no effect on frequency of ED use or the proportion of participants with ED use.…”
Section: Discussionsupporting
confidence: 69%
“…This heterogeneity can impede clinicians from promptly accessing up-to-date directives in emergency situations and result in the loss of ACP-related information during care transitions across health networks. Therefore, there is a clear need for centralized and standardized ACP recording . Standardizing ACP billing codes and incorporating consistent documentation as a crucial benchmark for cancer center accreditation can help achieve this goal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a clear need for centralized and standardized ACP recording. 20 Standardizing ACP billing codes and incorporating consistent documentation as a crucial benchmark for cancer center accreditation can help achieve this goal. The success of notable systemic ACP interventions supports systematic integration of ACP into specialty care and delivery models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations